Synthesis and Application of a Sulfonated Carbon Catalyst for a Hydrolisis Reaction - Efiyanti, Lisna; Indrawan, Dian Anggraini; Arif, Zulhan; Hutapea, Devandri; Septina, Ane Dwi (Indonesian Journal of Science and Technology, 2020)
Biomass, such as wood waste, is one of the resources that can be potentially converted into a carbon product for catalyst applications. In this study, the sulfonated carbon was obtained through the pyrolysis method for wood waste at the temperature of 350Â°C, which was later sulfonated through the use ofÂ  H2SO4 (8N) on the reflux for 4 h. The sulfonated carbon was then analyzed and characterized including its water content, ash content, volatile matter, fixed carbon, iodine adsorption as well as the H+ (acidity) capacity using ammonia adsorptions and functional groups and the Fourier Transform Infra-Red (FTIR) instrument. The catalyst application was carried out during the kempili pulp hydrolysis process using a microwave with the ratio of catalyst to a pulp of 1:1 (5g:5g), with the power conditions of 300, 400, and 600 watt for 3, 5, and 7 min. The results showed that the sulfonated carbon catalyst had water content, volatile matter, ash content, fixed carbon, iodine adsorption as well as the catalyst acidity as much as 3.48%; 11.70%; 4.21%; 84.62%; 690.88 mg/g; and 6.45 mmol/g, respectively with the highest glucose content of 160.83 ppm. The carbon-based catalyst is expected as an alternative catalyst, can be further developed for hydrolysis reactions, and can serve as a green technology product in the future.